Asymmetric Synthesis of 3-Lactone-Substituted 2-Oxindoles with Vicinal Quaternary Carbon Centers through Vinylogous Conjugate Addition - Li, Zegong; Zeng, Zi; Tang, Qi; Zhong, Ziwei; Liu, Xiaohua; Feng, Xiaoming (Synlett, 2023)
A new method has been developed for constructing vicinal quaternary stereocenters with an oxindole–butanolide hybrid framework through asymmetric vinylogous addition of a siloxyfuran to an indol-2-one in the presence of a readily available N,N′-dioxide–Ni(OTf)2 complex catalyst. Various oxindole–lactones were obtained in up to 98% yield with >19:1 dr and 97% ee under mild reaction conditions. A possible transition-state model is proposed to explain the origin of the asymmetric induction.
Keywords: asymmetric catalysis; nickel catalysis; ligands; bromooxindoles; lactones; vinylogous addition